BLENDED PROJECT BASED LEARNING: THINKING SKILLS OF NEW STUDENTS OF BIOLOGY EDUCATION DEPARTMENT (ENVIRONMENTAL SUSTAINABILITY PERSPECTIVE) - Husamah, H. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
This study aims to analyze the difference of thinking skills of treatment (using Blended Project Based Learning) and control classes. This is a quasi-experimental study at new students of Biology Education. The thinking skills difference between treatment and control known through statistical test (SPSS). The results showed that there was difference in thinking skills (self-regulated, critical, and creative thinking) between treatment and control. Mean of self-regulated thinking of treatment (16.0) was higher than control (13.4). Mean of critical thinking of treatment (19.7) was higher than control (16.7). Mean of creative thinking of treatment (14.3) was higher than control (11.8).